Pengaruh Penambahan Limbah Serbuk Kaca dan Limbah Serbuk Kayu Terhadap Kuat Tekan dan Daya Serap Air Paving Block - Erlangga, Muhammad Fadhil; Handayani, Dewi (Center for Environmental Research, LPPM, Universitas Sebelas Maret, 2023)
Garbage is one of the major factors in environmental pollution. When the waste management process is not proportionate to the amount of garbage generated, the impact of the accumulation of waste makes the pollution of waste more noticeable. Efforts undertaken in waste management, i.e. using glass waste and wood powder waste as sand subtitles on paving block manufacturing, are expected to reduce environmental pollution problems. The study aims to obtain the highest pressures strength values and the lowest water absorption on paving blocks with a variation of glass waste of 2.5%, 5%, 7,5%, 10%, 12,5% and wood powder of 10% as a subtitling of sand paving block mixed material. From the test results obtained the highest pressures strength value of the variation of mixture of glass powder 5% and wood powder 10% of 4.30 MPa. At the test results, the lowest water absorption was obtained from a variation of a mixture of 5% glass powder and 10% wood powder of 6.42%.